ayat-ayat argumentasi, ndzr, bashar dan ru’yah - Hussein, Sikna Jebur; Alaa Yaseen, Dina (STAI Al-Mujtama Pamekasan, 2025)
The holy Quran is precise in its meaning and pronunciation, for each pronunciation has its meaning and connotation, and a Quranic term varies in meaning according to the topic discussed, and context of the text it is present in.The sense of sight is one of the five senses that Allah (SWT) blessed his humans with, and the word look carries multiple meanings and connotations, such as looking with the eyes which means contemplating something inside the heart , and the word vision mean multiple things in the holy Quran as well, including seeing with the eyes, the heart, news, visions of thinking and contemplation, and sight of dreams. And in this paper we primarily look into research with the terms (look, sight, vision) and their occurrence in the versesof arguments , as it is a concept that is difficult to limit and understand.The Argumentative discourse the holy Quran was able to influence its followers by depending on strategic ways that address the mind and soul together as one, with the aim of attracting them, and guiding them prove the oneness and singleness of